Effect of the CCB-LE265 strain of the entomopathogenic fungus Beauveria bassiana Vuillemin, 1912 on Alphitobius diaperinus (Panzer, 1797) (Coleoptera: Tenebrionidae) from poultry farms in Huaral, Peru - Villanueva, Dulce (2025)
The objective of this study was to evaluate the effect of the CCB-LE265 strain of Beauveria bassiana Vuillemin, 1912 on adults of Alphitobius diaperinus (Panzer, 1797) (Coleoptera: Tenebrionidae). Adult beetles were collected in the populated center of 'San Graciano' in the Aucallama district, Huaral, Peru. After verifying the viability of the conidia, four treatments with B. bassiana were applied, designated as T1, T2, T3, and T4, each with a concentration of 1 x 10⁷ conidia·mL-1, 2 x 10⁷ conidia·mL-1, 3 x 10⁷ conidia·mL-1, and 4 x 10⁸ conidia·mL-1, respectively. The dead beetles were incubated for 21 days to promote mycelial growth and confirm whether the cause of mortality was attributable to B. bassiana. The results indicated that all treatments were pathogenic to A. diaperinus. Treatment four (T4) showed a significant difference in terms of mortality and was the most effective in inducing mycosis, with 17.71%. In contrast, the other treatments showed lower mycosis values. These findings suggest that B. bassiana has potential for use in future trials under poultry production conditions to control A. diaperinus populations.